Effect of high-tech swimsuits on the swimming performance in top-level swimmers - Issurin, V.; Pushkar-Verbitsky, V.; Verbitsky, O. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: This study was intended to evaluate the effect of high-tech swimsuits (HTS) on the swimming performance of top-level swimmers in the 50m. event. Special attention has been given to the assessment of HTS effects related to low resistance strokes (LRS: freestyle and backstroke) and high resistance strokes (HRS: breaststroke and butterfly). METHODS: The data was collected from a database of two subsequent World Swimming Championships in 2009 and 2011. In the 2009 World Swimming Championships (WSC) all athletes had used HTS, whereas in the 2011 WSC following the new regulation of the International Swimming Federation the HTS`s were excluded and all participants had utilized standard swimsuits only. This study`s database has been accomplished with performance times (PT) of the six leading female and male participants of the 50m. events; totaling 46 participants in 2009 and 45 participants in 2011 WSC. PT of preliminary, semifinal, and final events were tested using an unpaired t-test with Bonferroni-Holm correction. The Fisher`s exact test 2 x 2 was used to determine association between significant/insignificant changes in the PT and LRS/HRS. RESULTS: The 2x2 Fisher`s exact test demonstrates the difference between the LRS and HRS strokes for females and males with and without the HTS is statistically significant: P=0.021. For females only P=0.015, and for males only P=0.3863. CONCLUSION: The obtained results show that rejection of the HTS led to significant decrease of athletic performances. It was found that HTS gave more pronounced facilitation effect for men as compared with women, and for low resistance as compared with high resistance swimming strokes.